Simultaneous hydroconversion of n-Hexane and benzene over Pt/WO 3-ZrO2 in the presence of sulfur impurities - Busto, Mariana (2009)
The properties of a commercial Pt/WO3-ZrO2 for the simultaneous hydro-isomerization of n-hexane and benzene have been assessed at varying values of total system pressure, fixed reaction temperature (300 °C), and molar ratio H2/HC ) 6. A total pressure of 20 atm was satisfactory for performing both the hydrogenation of benzene and the isomerization of C6 at convenient reaction rates. Greater pressures increased the cracking and formation of light gases. Also, the total conversion was decreased at higher pressures. Benzene conversion proceeded by metal-catalyzed hydrogenation and subsequent acid-catalyzed ring contraction with no occurrence of ring opening. The results show that the presence of a small amount of benzene (3%, vol/vol) is beneficialfor the hydro-isomerization of n-hexane over Pt/WO3-ZrO2. Hydrocracking is largely suppressed, and both the liquid C5+ yield and the selectivity to branched isoparaffins are enhanced. Sulfur impurities in the feed decrease the n-hexane and benzene conversion by poisoning the metallic function, and their concentration should be lowered to less than 10 ppm to avoid producing an important inhibiting effect.